Maternal nutritional status in diabetes mellitus and neonatal characteristics at birth - Diane Bressan Pedrini; Maria Luzia Chollopetz da Cunha; Márcia Koja Breigeiron (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objectives: to analyze the nutritional status of women with diagnosis of Diabetes mellitus in pregnancy and the newborns' characteristics in relation to health conditions at birth. Methods: transversal study with data from 394 electronic medical charts (197 newborn and 197 mothers), between 2017 and 2018. Descriptive and analytical statistics. Results: there was prevalence of women with Gestational Diabetes (78.2%), followed by Type II Diabetes (13.7%) and Type I Diabetes (8.1%), and of term births (85.3%) and cesarean deliveries (54.8%). Type I Diabetes was associated to earlier gestational age at birth (p>0.001) and obesity during pregnancy was associated to higher birth weight of newborns (p=0.024). Clinical complications occurred in 37.6% of newborns. Among complications, Type I Diabetes was associated with respiratory disorder (p=0.005), and prematurity was associated with mother's overweight/obesity (p=0.010). Conclusions: we strongly advise about the need of metabolic and nutritional control during gestations that course with Diabetes mellitus, due occurrence of negative consequences to the newborn´s health at birth.